Descriptive study of functional outcome and complication of fracture calcaneum treated with locking calcaneum plate - Jain, Amit; Meena, R. C.; Choudhary, Laxman; Jain, Jitesh; Chandra, Abhishek; Sharma, Anurag; Bhati, Lokpal Singh (International Journal of Research in Orthopaedics, 2019)
Background: Fracture of calcaneum accounts for about 2% of all fractures and 75% of all calcaneum fractures are intra-articular. Numerous controversies existed regarding optimal treatment of displaced intraarticular calcaneum fractures. In this study evaluate post-operative functional outcome and complication of fracture calcaneum treated with locking calcaneum plate. Methods: This hospital based prospective descriptive study was conducted on 108 patients (120 calcaneum fracture) operated between July 2016 to December 2018 by open reduction and internal fixation with locking calcaneum plate through extensive lateral approach at Department of Orthopaedics, SMS Medical college and hospital, Jaipur. All close displaced intraarticular calcaneal fracture was included in the study. Results: Average duration between injury and surgery was 8.3±2.97 days. Out of 120 calcaneum fracture 52 fractures (43.33%) were Sander’s type II, 52 fractures (43.33%) were Sander’s type III, and 16 fractures (13.33%) were Sander’s type IV. Pain on weight bearing was noted in 20 patients (16.66%) implant prominence was noted in 8 patients and delayed wound healing was seen in 4 patients. Maryland foot score was excellent in 44 fracture (36.67%), good in 56 fractures (46.67%), fair in 8 fractures (6.67%), and poor in 12 fractures (10%). Conclusions: Open reduction and internal ﬁxation (ORIF) with locking calcaneum plate in an indicated case, with respect to soft tissue envelope and early rehabilitation, leads to better therapeutic results as compared to other operative technique.